STRATEGI DESAIN BERKELANJUTAN PADA BANGUNAN HOTEL BERBASIS KONSEP GREEN HOTEL - Pebriyanti, Ni Luh Putu Eka (Universitas Atma Jaya Yogyakarta, 2017)
Abstract: Application of the concept of sustainable development requires integration between the micro scale (building), meso scale (building group) and macro scale (city). Since 2008, ASEAN has rewarded hotels in the world that meet environmentally sound hotel standards. The Ministry of Tourism and Creative Economy has appreciated and organized the award of the National Green Hotel Award since 2011. This research focuses on identifying and analyzing sustainable design strategies at three hotels in Jakarta and Bali covering efficiency, conservation and management of various elements: land, energy , water, materials, air and indoor health, and environmental management. The analysis used normative architectural criticism approach on the standard study in designing hotel buildings that applied the concept of